What to Learn from Three Years (2018-2021) : Trends of Digital Platform Research - Seungyeon Ha; Jong Pyo Kim; Yu Jun Park (International Telecommunications Society (ITS), 2021)
In recent years, there has been a vigorous discussion on digital platform due to their emerging significance in the digital ecosystem. Despite common interests in digital platform, the comprehensive literature review on the topic is still limited. In addition, no study has examined whether there is a link or gap between research on digital platform and reality in global digital platform markets. This study aims to offer a systematic and interdisciplinary review of the literature on digital platforms by collecting and analyzing a sample of 703 articles published from January 2018 to January of 2021.
Keywords: 330; Digital Platform; Online Platform; E-Commerce Platform; Social Media Platform; Platform Hegemony; Interaction